Clinical pharmacology study of ipragliflozin in Japanese patients with type 1 diabetes mellitus: A phase 2, randomized, placebo‐controlled trial - Kaku, Kohei (Diabetes Obes Metab, 2019)
AIM: To evaluate the pharmacodynamics, pharmacokinetics, and safety of the novel oral sodium‐glucose co‐transporter‐2 inhibitor, ipragliflozin, in Japanese patients with type 1 diabetes mellitus. MATERIALS AND METHODS: We conducted a multicentre, double‐blind, placebo‐controlled, parallel‐group study. Patients were randomized to receive 25, 50, or 100 mg/day ipragliflozin or placebo for 2 weeks. Key pharmacokinetic endpoints included area under the concentration‐time curve 24 hours postdose (AUC(24h)), maximum plasma concentration (C(max)), and renal clearance. Key pharmacodynamic endpoints included 24‐hour urinary glucose excretion, mean plasma glucose AUC(0‐24h), and mean renal glucose clearance. Changes in total, basal, and bolus insulin dosages were recorded. Adverse events (AEs) were monitored for safety. RESULTS: Dose‐dependent increases were observed in AUC(24h) and C(max) on days 1 and 14 for 25‐, 50‐, and 100‐mg ipragliflozin. The mean plasma glucose AUC(0‐24h) was lower than that of placebo and the mean renal glucose clearance increased in a dose‐dependent manner from baseline, but remained unchanged in the placebo group. The mean (standard deviation) change from baseline in total daily insulin dose was greater in the ipragliflozin 25‐, 50‐, and 100‐mg groups (−14.77 ± 14.04%, −18.40 ± 12.49% and −19.25 ± 16.77%, respectively), than placebo (−4.51 ± 16.28%). Most AEs were mild in severity; no patients discontinued the study because of treatment‐emergent AEs. CONCLUSIONS: The pharmacokinetic and pharmacodynamic properties of ipragliflozin in Japanese patients with type 1 diabetes mellitus were confirmed. Increases in urinary glucose excretion lead to dose‐dependent decreases in plasma glucose. Concomitant insulin dose decreased with ipragliflozin treatment. No clinically relevant safety concerns were identified.